Abracadabra 3.0 / Aileen Farida Mohd Adam and Noraziah Mohd Amin - MohdAdam, Aileen Farida; Mohd Amin, Noraziah (Academy of Language Studies, 2022)
The Abracadabra 3.0 E-Poster Competition programme for PPT (pre-commerce and pre-science) students of UiTMCPP Permatang Pauh campus was held from 20 December 2021 till 19 January 2022. The programme is a poster presentation com-petition that aims to increase self-confidence and English lan-guage ability, especially for pre-diploma students. This programme is an annual programme organised by Academy of Language Studies, UiTM Penang Branch to strengthen pre-diploma students’ language skills. Getting a message through requires the ability to present information clearly and effectively. This is one of the criteria for the participants of Abracadabra 3.0 in order for them to win this e-poster presentation contest. PPT students who were taking the ELC010 (English for Pre-Diploma 1) and ELC030 (English for Pre-Diploma) courses showed off their poster presentation skills using this year’s theme ‘Traverse Malaysia 2022’ which offered contestants the opportunity to be more creative and observant in selecting a Malaysian attraction as their topic. 22 groups of students with 3 to 4 members each were selected from 11 classes. The selection process was carried out by their respective class lecturers. The programme was carried out fully online in which registration and submission of videos were done from 20 December 2021 to 7 January 2022. Meanwhile, evaluation was carried out between 8 to 18 January 2022 by seven juries consisting of English language lecturers from UiTM Penang.